The concept of productive ambiguity with some examples from Iliad 2 - Abritta, Alejandro (2022)
The goal of this paper is to introduce and elucidate the concept of “productive ambiguity” for the study of Homeric poetry and other literary texts. After the introduction, I present a theoretical elucidation of the concept, starting from a general notion of ambiguity and identifying three features of productive ambiguity: its irresolvable character (no alternative can be ruled out on textual or linguistic grounds), its persistence (both alternatives are appropriate to the context and contribute to the interpretation of the text), and its productivity (the ambiguity itself contributes to the interpretation of the text). In the third section, I analyze four passages from Iliad 2: 2.73, 285, 340-9, and 807, studying in each the source of the ambiguity and demonstrating that it fulfills the three features to be considered productive.